Scared stiff ebook - Ryan, Annelise (Mattie Winston Mystery, 2011)
A coroner becomes a sleuth when an innocent friend is accused of murder in this hardboiled mystery by the USA Today –bestselling author of Dead Even . When Deputy Coroner Mattie Winston and her boss/best friend, Izzy, are called to the home of waitress and part-time model Shannon Tolliver, they find the ghoulish Halloween decorations a bit too authentic. Among the fake blood and skeletons is the corpse of Shannon herself. Since the whole town knows Shannon recently had a very public spat with her estranged husband, Erik, he's suspect #1. But Mattie happens to know Erik truly loved his wife, and is simply incapable of the brutal act—even if he owns the exact same caliber handgun as the murder weapon . . . Determined to unearth the truth, Mattie puts her scalpel-sharp medical skills to work, and digs a little deeper. What she uncovers is stranger than anyone could have imagined . . . "Ryan shows growing skill at mixing humor with CSI-style crime."— Publishers Weekly "The forensic details will interest Patricia Cornwell readers . . .while the often slapstick humor and the blossoming romance between Mattie and Hurley will draw Evanovich fans."— Booklist